Academic productivity and its relationship with physical activity and job satisfaction - Cantell-Rojas, María Fernanda; Peña-Quimbaya, Eder; Campos-Uscanga, Yolanda; Argüelles-Nava, Vianey Guadalupe; Ramírez-Colina, Saraí; Ortiz-Chacha, Christian Soledad; Mota Morales, María de Lourdes (Horizonte Sanitario, 2024)
Objective: We aimed to determine whether academic productivity is related to physical activity and job satisfaction among the academic staff working for a public university located in Mexico. Materials and methods: A quantitative, cross-sectional, analytical and correlational study was carried out., the sample of 215 academics enrolled at Universidad Veracruzana, located in Veracruz, Mexico, non-probability quota sampling. We used both the 8-item Job Satisfaction Likert-type scale, and the 7-item International Physical Activity Questionnaire (IPAQ), short version, which provides information regarding the time spent doing physical activity (sedentary, light intensity, moderate intensity and vigorous), as well as socio-demographic and work-related items. The analysis was done using descriptive and inferential statistics with the IBM SPSS Statistics 26 software for Mac. Results: 263 academics were involved, the majority (68.1%), reported a medium level of job satisfaction, 41.4% reported sedentary physical activity. Those with high levels of academic productivity reported walking fewer days per week compared to those with lower levels. Job seniority was positively related to days walked for both the sedentary and active groups, but the strength of this association was much higher for the sedentary (r = 366) groups than the active (r = 186) groups. Conclusions: No relationship was found between higher levels of productivity and higher job satisfaction or higher physical activity, so the hypotheses are rejected. But it is shown that job characteristics such as work hours and job seniority, limit physical activity, especially for the 41.4% of the population classified as a sedentary population, posing some health risks because of the lack of physical activity.